2015
DOI: 10.1589/rika.30.47
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Energy Balance on Discharge to Home of Frail Elderly Persons in a Health Facility for the Aged

Abstract: This study examined the effect of energy balance on the discharge to home of frail elderly persons in a health facility for the aged. [Subjects] One hundred twenty-one frail elderly persons receiving residential care in a health facility for the aged. [Methods] Participants were divided into the following two groups: the discharge to home group (n=58), and the residential care group (n=63). We determined energy consumption, energy intake, energy balance, demographic data and the Functional Independence Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Older people with limited ability to perform ADLs, males, and those admitted from other institutions are more likely not to return home . When nutritional status was assessed, energy balance has also been shown to be significantly positive among subjects from homes compared with that in frail older adults living in LCHFs . Although it has been shown that nutritional intervention is effective for improving the physical function of older adults living in nursing homes, the direct impacts of nutritional status when assessed in LCHFs have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Older people with limited ability to perform ADLs, males, and those admitted from other institutions are more likely not to return home . When nutritional status was assessed, energy balance has also been shown to be significantly positive among subjects from homes compared with that in frail older adults living in LCHFs . Although it has been shown that nutritional intervention is effective for improving the physical function of older adults living in nursing homes, the direct impacts of nutritional status when assessed in LCHFs have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%